Designing better enzymes: Insights from directed evolution. (April 2021) - Bunzel, H. Adrian; Anderson, J.L. Ross; Mulholland, Adrian J.
Highlights: Enzymes can be created by computational design and directed evolution. Insights from directed evolution: Active-site organization by H-bonding networks and evolved energy landscapes. Electrostatic redesign accelerates directed evolution. Dynamical networks integrate the protein scaffold into catalysis. Abstract : De novo enzymes can be created by computational design and directed evolution. Here, we review recent insights into the origins of catalytic power in evolved designer enzymes to pinpoint opportunities for next-generation designs: Evolution precisely organizes active sites, introduces catalytic H-bonding networks, invokes electrostatic catalysis, and creates dynamical networks embedding the active site in a reactive protein scaffold. Such insights foster our fundamental knowledge of enzyme catalysis and fuel the future design of tailor-made enzymes.